SMOKESCREEN OVER CABIN AIR QUALITY BANNING OR REDUCING SMOKING ON BOARD AIRCRAFT MAY DISGUISE POOR VENTILATION - ENDRES,G (Tufts Archival Research Center, 2007)
Article discussing poor ventilation in airline cabins. Suggests that banning smoking on flights may be accompanied by a decrease in in-flight fresh air. Emphasizes that smoking is not the only health risk in airline cabins. Discusses occupational health risks of pilots and flight attendants due to exposure to poor indoor air quality.